Hubungan Stres dengan Motivasi Belajar Mahasiswa disaat Pandemi Covid-19 - Laras Ayu Savira; Octa Reni Setiawati; Ismalia Husna; Woro Pramesti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; The World Health Organization revealed on January 30, 2020 that the corona virus has become a Public Health Emergency of International Concern (PHEIC). Aim; know the relationship between stress and learning motivation. Methodology; quantitative type with analytic design and crosssectional approach. The measurement instrument used was the DASS 42 questionnaire (Depression Anxiety Stress Scales 42), a learning motivation questionnaire. Result; shows that the distribution of the highest stress variable with moderate stress level (43.3%) and the highest learning motivation variable with moderate learning motivation level (48.3%) and for the correlation analysis results on learning motivation. variable with stress obtained P = 0.000 and the results of the correlation coefficient r = -0.511. Conclusion; that there is a relationship between stress and learning motivation.